The Relevance of Criminal Close to the Modern Criminal Justice System (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
This study aims to know the application of cover-up punishment in Indonesia has been regulated and as a legal basis for cover-up punishment can be seen first of all in Act No. 20 of 1946. Coverage punishment as the main crime appears through Act No. 20 of 1946 RI News II No. 24. In this article, the punishment for imprisonment is added for the Criminal Code and the Criminal Code. This punishment can be imposed on perpetrators who have committed criminal acts, but are motivated by intentions that deserve respect. Covering this system of criminal threats of cover up, it is clearly not adhered to in the Criminal Code. With the development of regulations regarding criminal law which contain new and increasingly progressive provisions, cover-up punishment still fills a place in the current list of principal crimes. In fact, the Draft Criminal Code which is currently being discussed as the Priority National Legislation Program (Prolegnas) still contains the existence of a cover-up crime as a form of principal crime. Coverage punishment, if it is related to the purpose of punishment according to the new Criminal Code Concept, it appears that the most prominent purpose of covert punishment is the protection of society. Judging from the background of the establishment of a cover sentence, there is no similarity in moral ideas from previous and future events, there are no limitations on the extent to which the intention of deserving respect can be used.